IMPROVING THE PROFESSIONAL TRAINING OF THEIR STUDENTS IN THE CONDITIONS OF PEDAGOGICAL MODERATION - Ergasheva Barno Ziyavitdin qizi (Лучшие интеллектуальные исследования, 2024)
Annotation: This article will talk about the competence of students of the Department of Pedagogy in the conditions of development. The content of pedagogical quality and professional training, which should be mastered for future educators, is covered.